2004
DOI: 10.4049/jimmunol.172.9.5329
|View full text |Cite
|
Sign up to set email alerts
|

Latent Membrane Protein 2A, a Viral B Cell Receptor Homologue, Induces CD5+ B-1 Cell Development

Abstract: The latent membrane protein 2A (LMP2A) of EBV plays a key role in regulating viral latency and EBV pathogenesis by functionally mimicking a constitutively active B cell Ag receptor. When expressed as a B cell-specific transgene in mice, LMP2A drives B cell development, resulting in the bypass of normal developmental checkpoints. In this study, we have demonstrated that expression of LMP2A in transgenic mice results in B cell development that exclusively favors B-1 cells. This switch to B-1 cell development occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 67 publications
4
27
0
Order By: Relevance
“…The enhancement of survival seen in LMP2A-expressing cells results in altered B cell development phenotypes in some transgenic mouse models (24,27,33,34). We chose to use the Tg6 E LMP2A transgenic line used for the experiments in this article because it has normal B cell development that is indistinguishable from wild-type mice (27,33).…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of survival seen in LMP2A-expressing cells results in altered B cell development phenotypes in some transgenic mouse models (24,27,33,34). We chose to use the Tg6 E LMP2A transgenic line used for the experiments in this article because it has normal B cell development that is indistinguishable from wild-type mice (27,33).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of LMP2A interferes with BCR signaling and function. It has been demonstrated that low LMP2A expression does not inhibit Ig rearrangement, BCR expression or normal B-cell differentiation into follicular and marginal zone B cells, while high LMP2A expression inhibits BCR expression and results in exclusive B-1 differentiation in the bone marrow and peripheral lymphoid organs [49,86,87]. Most of the phosphotyrosine activity in latently infected B-cells is associated with LMP2A patches, and these clustered membrane patches mimic the activated BCR [70,82,88,89].…”
Section: The Bcr Blockade and Ubiquitin-mediated Pathwaymentioning
confidence: 99%
“…Several studies involving microsequence and mutation analysis and structural approaches showed that the HECT-domain containing the Nedd4 ubiquitin protein ligase family, which contains WW domains, participates in WW-PY interaction [54,55]. The ubiquitin protein ligase family includes AIP4/Itchy, WWP2, Nedd4 and KIAA0439/Nedd4-2 [49,56,57]. Microarray analysis has identified a number of LMP2A-mediated transcriptional changes in the genes encoding ubiquitination [58].…”
Section: The N-terminal Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, LMP2A is essential for growth transformation of germinal center (GC)-derived BCR − B cells (13). Depending on its B-cell expression level in murine models, constitutive LMP2A expression alters B-cell development or augments the differentiation and activation of antigen-driven B cells (9,10,(14)(15)(16).…”
mentioning
confidence: 99%